2020
DOI: 10.34087/cbusbed.773244
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Effects of Chronic Stress on Adrenal Gland by Using Morphometric and Histochemical Methods on Rats Model

Abstract: Vücuda çeşitli hasarlar veren stres faktörlerine karşı organizmada yanıt oluşturan yapıların başında nöroendokrin sistemin geldiği bilinmektedir. Biz de sıçanlarda kronik stres modeliyle adrenal bezlerde oluşabilecek morfolojik ve histolojik değişiklikleri araştırmayı amaçladık. Gereç ve Yöntemler: 24 Sprague Dawley sıçan, her birinde 6'şar erkek veya dişi sıçan olan 4 gruba ayrıldı. 14 gün, dişi ve erkek kontrol gruplarına hiçbir uygulama yapılmazken, stres gruplarına kronik stres prosedürü uygulandı. Sıçanla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Studies on the effects of paracetamol on the thyroid gland are limited, but many studies have shown that different agents such as medications 14,15 , stress 16 heavy metals 17 and pesticides 18 have structural and functional effects on the thyroid gland. In the present study, colloidal degeneration of thyroid glands, epithelial cell deposition in the lumen, deformity of follicles, disturbances in the colloidal area, and follicle epithelium spills were observed in the thyroid glands of paracetamol groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of paracetamol on the thyroid gland are limited, but many studies have shown that different agents such as medications 14,15 , stress 16 heavy metals 17 and pesticides 18 have structural and functional effects on the thyroid gland. In the present study, colloidal degeneration of thyroid glands, epithelial cell deposition in the lumen, deformity of follicles, disturbances in the colloidal area, and follicle epithelium spills were observed in the thyroid glands of paracetamol groups.…”
Section: Discussionmentioning
confidence: 99%